Status and trends of graduate library and information science researches submitted to library schools in Metro Manila, 1992-2007 - Dery, Zipporah M.; Faderon, Rosalie B.; Mallari, Florenda D. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2010)
Research performs a vital role in the development of library and information science (LIS) because it informs the theory and practice of the field through a systematic method of inquiry. Analysis of the content of LIS researches could reveal the state and direction of research initiatives as well as the needs and potentials of LIS research towards the development of the LIS theory and practice. It is in this light that this study delved on the status and trends of graduate LIS researches submitted to library schools in Metro Manila from 1992 to 2007.
Content analysis was performed on researches submitted to library schools in Metro Manila in partial fulfillment of the requirements for a graduate degree or graduate major in LIS from 1992 to 2007. It examined the researches' orientation to basic and action research, the research topics tackled most and least and the research methodology, sampling, research instrument, and statistical analysis technique utilized most and least.
This study found out that (a) all researches were oriented towards action research; (b) broad topics discussed the most were Libraries and Information Centers, Library Use and Users, and Organization while broad topics discussed the least were Librarianship and Information Science, Library Buildings, Other Fringe Subjects, Media, and Knowledge Learning; (c) survey was the research methodology employed the most while causal comparative was utilized the least; (d) regarding sampling techniques, the involvement of the entire population was employed the most while the combination of sampling techniques was used the least; (e) questionnaire was the research instrument employed the most while test was utilized the least; (f) descriptive statistics was the statistical analysis used the most while statistical techniques not identified were employed the least; (g) a positive trend was demonstrated by the following variables: broad topics 2.0 Profession, 3.0 Libraries and Information Centers, 4.0 Library Use and Users, 5.0 Materials, 6.0 Organization, 8.0 Library Technology, and 12.0 Bibliographic records; survey; probability sampling, non-probability sampling, the entire population, and sampling techniques not identified; questionnaire, interview schedule, and worksheet; and descriptive and inferential statistics; (h) researches submitted to CEU and UP shared similar positive trend in the study of broad topics 3.0 Library and Information Centers and 4.0 Library Use and Users and the use of descriptive statistics; (i) studies submitted in partial fulfillment of the the requirements for both graduate degrees shared a positive trend in the study of broad topics 3.0 Library and Information Centers, 4.0 Library Use and Users, and 6.0 Organization and in the use of survey, questionnaire, and descriptive statistics.
Conventional practices in LIS research were observed in this study, such as the conduct of action research, the study of topics commonly researched, and the use of conventional research method, instrument, and statistical analysis technique. A research agenda was recommended to be considered by the members of the LIS community to curve the research trends, encourage the study and use of nonconventional topics and methods, and respond to the needs and potentials of graduate LIS research.
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Library schools -- Philippines -- Manila Metropolitan Area; Library science -- Research -- Philippines -- Manila Metropolitan Area